Pendampingan Pembuatan Nomor Induk Berusaha sebagai Pendukung Pengembangan Usaha Mikro Kecil dan Menengah (UMKM) di Lorong Wisata - Hardianti Hafid; Moeh Zainal Khairul; Abd. Hafid; Rosmalah (Ininnawa : Jurnal Pengabdian Masyarakat, 2023)
MSMEs play a strategic role in the economy of Makassar City, particularly in Lorong Wisata. However, many MSMEs in Lorong Wisata face challenges in developing their businesses due to limited access to necessary resources and support. One of the main obstacles faced by MSMEs is the process of obtaining the Business Identification Number (NIB). This community engagement activity aims to examine the importance of guidance in the NIB application process as an effort to support the development of MSMEs in Lorong Wisata, Makassar City. The community engagement activity involved several MSMEs in Lorong Wisata, located in the Ballaparang Village, Rappocini District. The results of the engagement activity indicate that guidance in the NIB application process has a significant positive impact on the development of MSMEs in Lorong Wisata, Makassar City. This guidance includes assistance in document collection, form filling, communication with relevant agencies, and understanding of the procedures involved. With the guidance provided, MSMEs can overcome administrative barriers that often hinder their access to broader resources and opportunities. The guidance activity in NIB application plays a crucial role in supporting the development of MSMEs in Lorong Wisata, Makassar City. With guidance, MSMEs can enhance their access to support and opportunities, ultimately contributing to local economic growth and the improvement of the local community's well-being. The recommendation from this community engagement activity is the need for cooperation between the government, MSME support institutions, and the local community to provide effective and sustainable guidance for MSMEs in Lorong Wisata, Makassar City. Keywords: Cooperatives, MSMEs, Lorong Wisat